ChemInform Abstract: N‐Heteroarylation of Chiral α‐Aminoesters by Means of Palladium‐Catalyzed Buchwald—Hartwig Reaction. Issue 1 (7th January 2014) - Hammoud, Hassan; Schmitt, Martine; Blaise, Emilie; Bihel, Frederic; Bourguignon, Jean‐Jacques
Abstract The title reaction allows an efficient approach to a number of N‐arylated α‐aminoesters which are putative peptidomimetics.